Reimagining Education: The Open University and Social Mobility in Contemporary British Fiction - Piotr Biegasiewicz (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej)
This study examines how the Open University (OU) is portrayed in modern British literature, focusing on its role in enabling social mobility. Through an analysis of novels, plays, and short stories published since 1970, the research explores the OU’s depiction as a vehicle for socio-economic advancement, while also addressing broader cultural and policy debates on adult education and class.Using cultural materialist and adult education theories, the study identifies recurring themes such as personal transformation, class barriers, and the complexities of distance learning. It finds that literary portrayals of the OU often highlight its inclusive mission but also underscore systemic obstacles like financial constraints, social stigma, and institutional challenges. Additionally, the research examines how evolving education policies and public perceptions shape these narratives, reflecting societal attitudes toward open-access education. By bridging literary criticism with educational policy analysis, the study contributes to interdisciplinary scholarship, offering insights into the OU’s cultural significance in promoting equity. The research also suggests future directions, including examining young adult fiction featuring the OU and comparing representations of open universities globally. Ultimately, the OU’s depiction in fiction mirrors both the aspirations and challenges of adult learners in a stratified society.